Xanthine Oxidase Inhibitors from Garcinia esculenta Twigs - Zhu, Lun-Lun; Fu, Wen-Wei; Watanabe, Shimpei; Shao, Yi-Nuo; Tan, Hong-Sheng; Zhang, Hong; Tan, Chang-Heng; Xiu, Yan-Feng; Norimoto, Hisayoshi; Xu, Hong-Xi (Planta Medica, 2014)
The EtOAc-soluble portion of the 80 % (v/v) EtOH extract from the twigs of Garcinia esculenta exhibited strong xanthine oxidase inhibition in vitro. Bioassay-guided purification led to the isolation of 1,3,6,7-tetrahydroxyxanthone (3) and griffipavixanthone (8) as the main xanthine oxidase inhibitors, along with six additional compounds (1, 2, 4–7), including two new compounds (1 and 2). This enzyme inhibition was dose dependent with an IC50 value of approximately 1.2 µM for 3 and 6.3 µM for 8. The inhibitory activity of 3 was stronger than the control allopurinol (IC50 value: 5.3 µM). To our knowledge, compound 8 is the first bixanthone that demonstrated potent XO inhibitory activity in vitro. The structures of the new compounds were established by spectroscopic analysis, and the optical properties and absolute stereochemistry of racemic (±) esculentin A (2) were further determined by the calculation of the DP4 probability and analysis of its MTPA ester derivatives.
Keywords: Garcinia esculenta; Clusiaceae; xanthine oxidase inhibitor; 1,3,6,7-tetrahydroxyxanthone; griffipavixanthone